Community social barriers to non-technical aspects of flood early warning systems and NGO-led interventions: The case of Pakistan - Shah, Ashfaq Ahmad; Ullah, Ayat; Khan, Nasir Abbas; Khan, Abid; Tariq, Muhammad Atiq Ur Rehman; Xu, Chong (Frontiers in Earth Science, 2023)
Floods are the most common natural hazard in Pakistan, and research on flood risk management is continuously growing to improve policies for effective flood risk management. One of the critical determinants of effective food risk management is better communication of flood risks through the Flood Early Warning System. FEWS have been implemented widely; however, not all at-risk residents have been prompted to take immediate action in response to these alerts. This research looks at community social barriers to the non-technical aspects of FEWS and what Non-Governmental Organizations could do to address these gaping holes. This study used data from a field survey carried out in the four most severely affected districts of Khyber Pakhtunkhwa Province to explore gaps in non-technical aspects of flood early warning systems in Pakistan. The data were acquired through a comprehensive, structured questionnaire (600 household heads in total-150 HHs from each region) and focus group discussions with community leaders and elders (FGDs = 6), NGOs professionals (FGDs = 2) along with more casual exchanges over the phone. The data were analyzed using descriptive statistics and qualitative content analysis. The survey results found that most sampled respondents reported a lack of access to necessities, failure to heed flood alerts, misreading alerts, and poor connection between producers and consumers challenges under warning distribution and communication. Similarly, the critical challenges reported under the preparedness component were the exclusion of social groups from emergency preparedness, uncustomary contingency plans, and lack of political will. Furthermore, the key challenges included limited resources, risk perceptions, and a sense of belonging to ancestral lands under the response capability component. This paper finds that NGOs serve as a bridge between local communities and key disaster management institutions by tailoring solutions to individual community needs, educating necessary authorities about disaster risk reduction, facilitating communication among susceptible populations and authorities, and raising awareness through campaigns. Based on these results, we suggest authorities improve FEWS by improving communication infrastructures, translating early warnings into local languages, and developing a two-way information exchange system between stakeholders and contemporary emergency response plans.